Expedited Partner Therapy in Female Adolescents: A Study of Acceptance and the Impact on Reinfection Rates. Issue 11 (November 2021) - Gannon-Loew, Kathryn E.; Holland-Hall, Cynthia; Ebersole, Ashley M.; Alexy, Emily; Jackson, Kenneth; Bonny, Andrea E.
Abstract : Background: Given the high risk of sexually transmitted infections (STIs) in adolescents and young adults (AYAs), this study evaluated expedited partner therapy (EPT) acceptance and STI reinfection rates in female AYA before and after availability of EPT. Methods: The pre-EPT cohort was a 3-year (November 2012 to November 2015) retrospective chart review of female AYA positive for Chlamydia trachomatis (CT) and/or Trichomonas vaginalis (TV) before introduction of EPT. An EPT protocol for CT and TV infections was implemented after legalization in Ohio in 2016. The post-EPT cohort was a prospective review of patients positive for CT and TV for 2 years (5/2016–5/2018) after EPT introduction. We evaluated EPT acceptance and compared reinfection rates (positive test 1–6 months after initial infection) in the pre-EPT versus post-EPT cohorts and by EPT acceptance. Results: Among patients offered EPT, 28% (67/237) with CT and 25% (24/97) with TV accepted EPT. There were no significant differences in the reinfection rates for CT or TV in the pre-EPT versus post-EPT cohorts (CT: 24% (57/240) vs 20% (38/192), P = 0.42; TV: 23% (22/97) versus 14% (12/87), P = 0.11). Although lower, reinfections rates were not significantly different among patients who accepted versus did not accept EPT (CT, 13% (6/48) vs 21% (23/110), P = 0.50 and TV, 6% (1/18) vs 18% (9/49), P = 0.69). Conclusions: Despite the implementation of an EPT protocol, STI reinfection rates among female AYA remained high, and many declined EPT. Further research is needed to identify barriers to the provision and acceptance of EPT and ways to address these factors. Abstract : After introduction of expedited partner therapy to a female adolescent population, acceptance was low, and there were no significant differences in reinfection rates of Chlamydia trachomatis and Trichomonas vaginalis .